(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
We have concluded that the controller utilises cutting-edge technology to regulate power distribution, battery charging, and motor control, thereby enhancing the project’s sustainability and performance. The controller provides the vehicle with the necessary information to move and supplies the parts with the required power. We have examined the existing controller in the car and an alternate controller to determine which one would be more effective in enhancing the car’s performance. They had several traits that were better than the controller. We compared the two controllers, and the car worked better with the proposed controller. MATLAB simulations have been used to figure out the waveform.